What are the Current Opinions and Perceptions of Clinical Staff towards Caring for Obese Patients? Key Debates and Issues: A Qualitative Research Study in a Cardiac Centre in Bahrain - Goodwin, Sandra; Abouzaid, Catherine (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2017)
This study was conducted in a Cardiac Center in Bahrain. The cessation of obesity in the country is very high (Ministry of Health, 2012) and according to the World Health Organization (nd) obesity related diseases has been the cause of concern among men and women, also related disease such as cardiovascular, diabetes and chronic respiratory diseases are rising dramatically.